Challenges of implementing tenofovir disoproxil fumarate in pregnancy for prevention of hepatitis B mother to child transmission in a rural population - Bierhoff, M; Yotyingaphiram, W; Pimanpanarak, M; van Vugt, M; Rijken, M; Angkurawaranon, C; Nosten, F; Ehrhardt, S; Thio, C; McGready, R (Elsevier, 2020)
Background: Hepatitis B is highly endemic in south-east Asia with the most common route of transmission being from mother to child. In rural settings, current preventive strategies with hepatitis B immunoglobulins and vaccinations fail due to costs, need for cold chain, homebirths, and transportation difficulties. A new strategy for prevention of mother to child transmission (PMTCT) could be early (<20 weeks gestation) daily tenofovir disoproxil fumarate (TDF), a potent antiviral agent that is safe in pregnancy. Assessment of barriers to early TDF for PMTCT-Hep B is important before possible implementation. Methods & Materials: Narrative and visual review of start-up challenges encountered during implementation of a study of TDF for PMTCT before 20 weeks gestation in rural areas on the Thailand-Myanmar border. ClinicalTrials.gov Identifier: NCT02995005. Results: Major challenges of implementation from June 2018 to September 2019 included: gestation of pregnancy at presentation, point-of-care (POC)-testing reliability, tablet storage and handling. Overall, 156 women tested positive for HBsAg by Rapid Diagnostic Test (RDT) POC-testing but late presentation (≥20 weeks) was common: 53% (83/156). In women <20 weeks gestation with positive-HBsAg, consent for study screening was 89.0% (65/73). Exclusion after RDT-testing was 21.5% (14/65): three had a negative HBsAg at confirmation, nine had an undetectable viral load, two had elevated phosphate levels. Daily ambient temperatures were high: only 3/365 days (0.8%) were within manufacturer recommended TDF storage temperatures (20–25 °C), and for 187 days of the year the temperature was 30 °C. Drug accountability was high but one in 10 of the women reported incidents of tablet misplacement: “pills dropped though the [bamboo] floor and fell in the mud”, “children played with the bottle”. Financial support of transportation resulted in follow-up rates of 84.3% (43/51) attending all of the expected appointments. The missed appointments were highest in rainy season when the rivers become impassable, 62.5% (5/8). Conclusion: Improved public awareness of the benefits or early antenatal care, better RDT-tests, and confirmation of TDF bioavailability at higher ambient temperatures, are important in the rural tropics for prevention of mother to child transmission for hepatitis B programs.